Insights into second language reading : - Koda, Keiko (Cambridge University Press, 2005)
This critical volume, provides an in-depth analysis of second language reading's multiple dimensions. The paperback edition describes the complexity of reading and explains how reading differs in a first and second language. The book is broad in scope, covering all major aspects of the reading process and synthesizing all current reading research. The author provides a cross-linguistic orientation, explaining how first and second languages can mutually facilitate one another. This important volume offers strategies for enhancing literary acquisition, second-language learning and bilingual processing, and will serve as a valuable guide for graduate students, professors, researchers and foreign language teachers.